The impact of dietary protein: lipid ratio on growth performance, fatty acid metabolism, product quality and waste output in Atlantic salmon (Salmo salar) - Mock, Thomas S; Francis, David S; Jago, Matthew K; Glencross, Brett D; Smullen, Richard P; Keast, Russell S J; Turchini, Giovanni M (Aquaculture, 2019)
A common strategy for aquafeed manufacturers has been the utilisation of relatively large amounts of terrestrial, both animal and plant, oil sources to produce diets with a high energy content. The provision of high fat diets is aimed at promoting the utilisation of energy from lipid, thus increasing the amount of dietary protein used for tissue synthesis. However, in recent years the cost of marine sourced dietary lipids has risen, at the same time, farming operations are under increasing pressure to limit environmental degradation associated with nitrogenous waste effluent. Currently there is limited information available regarding the environmental and economic impacts of an altered dietary protein: lipid ratio in diets for large Atlantic salmon (Salmo salar) reared in seawater, presenting a potential impediment for nutritional based solutions. Accordingly the present study compared two isoenergetic diets with varied protein: lipid ratios via an assessment of growth, fatty acid utilisation, human nutritional quality, nitrogenous waste output and economic considerations. The trial diets were fed to the fish for the final 150 days of an on-farm grow-out period and resulted in minimal differences in fish growth, fatty acid utilisation and fillet quality. A decreased dietary protein: lipid ratio resulted in a more efficient protein utilisation both in terms of digestibility and assimilation into fish and, therefore, nitrogenous waste output was reduced. However, due to small differences in feed utilisation, the cost of fish production was numerically higher.